Perancangan Sistem Informasi Manajemen Invoice Menggunakan Generator Freamwork Django-Python Berbasis Website Pada Pt. Lampuind Tekno Elektrik - Risyda, Fitria; Nuryamin, Yamin (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2023)
Rapid technological advances encourage every company to keep abreast of developments and continue to improve its ability to manage data and information. Lampuind Tekno Electric companies currently still manages financial data and invoices by manually. This is prone to causing errors in typing invoices and loss of customer transaction data. For this reason, we need a system that helps in managing invoice data so that invoice data processing becomes faster and more accurate. The method used in the development of this application uses the waterfall Â model, the author makes the application design with the django Python framework and the modeling language uses the Unified Modeling Language (UML). With the existence of a web-based invoice management information system, it is hoped that it can assist employees in making invoices more quickly and accurately as well as making it easier to search for data and present information.